Incorporation of whatsapp and other similar electronic messaging applications into criminal proceedings during the pre-trial phase (Acta Judicial Journal, 2022)
This article deals with the anomalous incorporation into the criminal procedure of the content of the conversation or message generated through instant messaging applications and its evidentiary effects from the perspective of the public faith competences of the Judicial Clerk.